2010
DOI: 10.1681/asn.2009070741
|View full text |Cite
|
Sign up to set email alerts
|

CCR6 Recruits Regulatory T Cells and Th17 Cells to the Kidney in Glomerulonephritis

Abstract: T cells recruited to the kidney contribute to tissue damage in crescentic and proliferative glomerulonephritides. Chemokines and their receptors regulate T cell trafficking, but the expression profile and functional importance of chemokine receptors for renal CD4 ϩ T cell subsets are incompletely understood. In this study, we observed that renal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
180
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 163 publications
(187 citation statements)
references
References 33 publications
6
180
1
Order By: Relevance
“…Moreover, in an in vivo migration experiment, we clearly demonstrated that CXCR3-deficient Tregs were less frequent in the liver of congenic mice upon Con A challenge compared with wt Tregs, verifying an impaired migration capacity of Tregs lacking CXCR3. It has to be remembered that non-lymphoid tissue-homing Tregs also express further chemokine receptors beside CXCR3 (e.g., CCR5 and CCR6), which might also account for Treg recruitment to the inflamed site (27)(28)(29)(30). Hence, we did not expect a complete lack of Tregs in the liver of CXCR3 2/2 mice, and, moreover, a total loss of Treg recruitment to target tissue might have resulted in an even more pronounced phenotype of naive CXCR3 2/2 mice.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in an in vivo migration experiment, we clearly demonstrated that CXCR3-deficient Tregs were less frequent in the liver of congenic mice upon Con A challenge compared with wt Tregs, verifying an impaired migration capacity of Tregs lacking CXCR3. It has to be remembered that non-lymphoid tissue-homing Tregs also express further chemokine receptors beside CXCR3 (e.g., CCR5 and CCR6), which might also account for Treg recruitment to the inflamed site (27)(28)(29)(30). Hence, we did not expect a complete lack of Tregs in the liver of CXCR3 2/2 mice, and, moreover, a total loss of Treg recruitment to target tissue might have resulted in an even more pronounced phenotype of naive CXCR3 2/2 mice.…”
Section: Discussionmentioning
confidence: 99%
“…To quantify glomerular and tubular tissue damage, PASstained kidney sections were evaluated as previously described. 9 The frequency of glomerular crescent formation on day 7 of NTN was significantly increased in Foxp3 YFP-Cre x Il10 flox/flox mice, which selectively lack IL-10-producing Tregs, in contrast to IL-10-competent Il10 flox/flox mice ( Figure 5, A and B). This effect was more pronounced 14 days upon induction of NTN ( Figure 5C).…”
Section: Aggravated Ntn In Mice Lacking Il-10-producing Tregsmentioning
confidence: 95%
“…Primer pairs were used as described previously. 9,11 Relative mRNA levels were calculated after normalization to 18S rRNA using CFX96 Manager software.…”
Section: Real-time Qualitative Rt-pcr Analysismentioning
confidence: 99%
See 2 more Smart Citations